Influence of Social Cognitive Cooperation Model with Techniques of Cognitive Restructuring and Engineering Modeling on Self Abasement Students - Ni Putu Nia Diastuti; Dewi Arum MWP; I Ketut Dharsana (Department of Guidance and Counseling, FIP, Undiksha, 2017)
This research is a quasi research (